The Influence of Financial Technology and Digital Marketing on Customer Satisfaction of Aroma Bakery and Cake Shop ( Case Study of Generation Z Lubuk Pakam) : Pengaruh Teknologi Keuangan dan Pemasaran Digital terhadap Kepuasan Pelanggan Aroma Bakery and Cake Shop (Studi Kasus Generasi Z di Lubuk Pakam) - Stevani Willia; Ade Gunawan; Dedy Lazuardi (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
This study aims to analyze the effect of financial technology and digital marketing on customer satisfaction at Aroma Bakery and Cake Shop, Bakaran Batu branch. The population for this study consists of 22,388 Generation Z individuals (aged 14–28 years old) in Lubuk Pakam, and quantitative data is used. Using the Slovin formula, 100 Generation Z respondents were obtained. The questionnaire data was tested for validity and reliability using Cronbach's alpha, then the data was analyzed using normality tests, multiple linear regression, multicollinearity, T-tests, F-tests, and determination coefficient calculations (R²). The regression equation Customer Satisfaction = 7.347 + 0.371 Fintech + 0.424 Digital Marketing + e means that both variables have a positive effect. The results of the study show that fintech and digital marketing have a positive and significant effect on customer satisfaction. Fintech (t = 4.395 sig < 0.05), with its ease, practicality, trust, speed, and transaction security of fintech, can improve customer experience and satisfaction. Digital marketing has a positive and significant effect (t = 6.539, sig < 0.05), proving that content marketing, influencer marketing, and digital discount vouchers are effective in increasing customer engagement and satisfaction. Simultaneously, the coefficient of determination of 61% indicates that the variables studied contribute significantly to customer satisfaction.